Indonesia’s Diplomacy for Papua Issue in the Melanesian Spearhead Group: Challenges Remain - Dugis, Vinsensio; Wardhani, Baiq (Universitas Muhammadiyah Yogyakarta, 2025)
Support from a number of South Pacific countries to groups that voice out the Papuan secession from Indonesia has long been disrupting the Indonesian government. Various policy measures aimed at responding to these continue to be taken, including through Indonesia’s participation as a member of the Melanesian Spearhead Group (MSG). This article analyzes the extent to which MSG is basically strategic for Indonesia, especially within the context of the Papuan secession issue, and how far Indonesia’s diplomacy through MSG has contributed to its main objective. Simultaneously utilizing an inter-governmental approach and strategic realism as a framework for analysis, it is argued here that while MSG has a politically strategic position prompting the Indonesian government to exploit similarities and differences with the Melanesian group of states, Jakarta’s diplomacy through MSG continues to face challenges in the future.